Evaluation of various waste cooking oils for biodiesel production: A comprehensive analysis of feedstock. (December 2021) - Sharma, Priyanka; Usman, Muhammad; Salama, El-Sayed; Redina, Margarita; Thakur, Nandini; Li, Xiangkai
Graphical abstract: Highlights: High VS (>97%) and carbon (60–84%) indicated the organic nature of WCOs. Long chain fatty acids having 16 and 18 carbon were abundantly present in all WCOs. FTIR confirmed the presence of functional groups related to lipids. Biodiesel derived from WCOs falls under the international biodiesel standards. Abstract: Biodiesel production from edible sources faces several challenges such as food security and cost issues. Waste cooking oils (WCOs) can be an alternative feedstock due to their large production. The comprehensive characterization of WCOs has been rarely reported in previous studies. In this study, six different WCOs including chicken oil (CO), fat, oil, and grease (FOG), beef hotpot oil (BHP), mixed waste cooking oil (MWO), duck oil (DO), and vegetable hotpot oil (VHP) were assessed for the biodiesel production. Lipid content of WCOs ranged from 73 to 84.5% with the highest C16 in DO (32.1%) and C18 in VHP (71.4%). The highest saturated (such as C16:0 and C18:0), monounsaturated (such as C18:1) and poly unsaturated (such as C18:2, and C18:3) fatty acids were 58%, 59%, and 21% in BHP, VHP, and MWO, respectively. The diverse nature of fatty acids in WCOs makes it highly recommended for biodiesel production, as its derived biodiesel complied with international standards. Fourier transform infrared spectroscopy confirmed the presence of linkages specific to lipid and thermogravimetric analysis showed high volatile matter content (>97%). Biochemical composition, fatty acids profile, and the properties of the produced biodiesel demonstrated that these WCOs could be promising candidates for biodiesel production, solving waste management and socio-economic challenges of conventional feedstocks. However, the commercialization of WCOs' biodiesel requires further investigation of produced biodiesel and their petro-diesel blends on the engine performance, efficiency, and emissions (SO×, NO×, and CO× ) parameters to produce quality and cost-effective biodiesel.